2021
DOI: 10.1155/2021/6630232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravenous Lidocaine on Inflammatory and Apoptotic Response of Ischemia‐Reperfusion Injury in Pigs Undergoing Lung Resection Surgery

Abstract: Background. Ischemia-reperfusion injury is one of the most critical phenomena in lung transplantation and causes primary graft failure. Its pathophysiology remains incompletely understood, although the inflammatory response and apoptosis play key roles. Lidocaine has anti-inflammatory properties. The aim of this research is to evaluate the effect of intravenous lidocaine on the inflammatory and apoptotic responses in lung ischemia-reperfusion injury. Methods. We studied the histological and immunohistochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Moreover, lidocaine pretreatment combined with dexmedetomidine can effectively improve the oxidative stress injury induced by NADPH oxidase, nNOS, and iNOS via decreasing the expression of related proteins. ( 23 ) Lidocaine was also protective against ischemia-reperfusion injury of lung ( 24 ) and brain ( 25 ) in animal models. With regard to anti-inflammatory activity, elevated plasma levels of IL-6, IL-8, complement C3a, and IL-1ra as well as expression of CD11b, L- and P-selectin, and platelet-leukocyte aggregates were significantly attenuated by systemic lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, lidocaine pretreatment combined with dexmedetomidine can effectively improve the oxidative stress injury induced by NADPH oxidase, nNOS, and iNOS via decreasing the expression of related proteins. ( 23 ) Lidocaine was also protective against ischemia-reperfusion injury of lung ( 24 ) and brain ( 25 ) in animal models. With regard to anti-inflammatory activity, elevated plasma levels of IL-6, IL-8, complement C3a, and IL-1ra as well as expression of CD11b, L- and P-selectin, and platelet-leukocyte aggregates were significantly attenuated by systemic lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is widely used intravenously in different species to provide analgesia and as an adjunct to general anesthesia. In one experimental model of lung transplantation, intravenous lidocaine was associated with an attenuation of the histological markers of lung damage in the early stages of reperfusion [62]. Administration of lidocaine may help to prevent lung injury during surgery with one lung ventilation, reducing the expression of proinflammatory cytokines and lung apoptosis [63].…”
Section: Local Anestheticsmentioning
confidence: 99%
“…Besides the applications as local anesthetic or antiarrhythmic, different studies that evaluated the administration of intravenous lidocaine in a perioperative way showed that it exerts positive effects by attenuating the inflammatory response [ [14] , [15] , [16] ]. Interestingly, it has been shown that intravenous lidocaine administration attenuates inflammation of the lower respiratory tract in an ischemia-reperfusion injury model [ 17 ].…”
Section: Introductionmentioning
confidence: 99%